Innovative work behaviour: An integrative investigation of person-job fit, person-organization fit, and person-group fit - Emiliana Sri Pudjiarti; Prihatin Tiyanto Priagung Hutomo (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
In relation to the problem of SME productivity, it is necessary to investigate whether there is a problem of mismatch between workers and work and groups and corporate cultural values. This study aims to analyze whether the concept of innovative work behavior can mediate the relationship of person-job fit, person-organization fit and person-group fit to job performance. The study was conducted in the metal SME industry in Tegal Regency, with 256 respondents. Data collection tools use questionnaires and interviews. Data analysis is done with a structural equation model. Based on the results of the analysis, there is a positive relationship between variables. This illustrates that the challenges of SMEs in the future are to maintain the best human resources to remain committed to the organization. In maintaining its existence, alignment of individual values with work, organization and groups is the best tool to achieve goals through innovative changes in employee behavior, and also to lay a solid foundation in the recruitment and selection process of new employees that have the potential to increase job performance.
Keywords: M52; M54; 650; HR development; employee engagement; person-fit-organization; competitiveness